Giving Sisyphus a Helping Hand : Pathways for Sustainable RIA Systems in Developing Countries - Ladegaard, Peter (World Bank, Washington, DC, 2018)
Regulatory impact assessment is a tool used by governments to support evidence-based and coordinated policy making. This paper contributes to the debate on regulatory impact assessment in developing countries by addressing the lack of a systematic account of reforms, and the lack of a comprehensive explanatory account of reform outcomes. The study first maps developing countries' regulatory impact assessment reforms between 2001 and 2016. In total, 60 reforms are identified. Reform design is analyzed by measuring adherence to six internationally recognized "good practices." The study then assesses whether the reforms -- two years or more after they were launched -- led to functioning regulatory impact assessment systems. Of the 60 reforms, 20 led to functional systems within two years of the conclusion of the reform. Three reforms were too recent to be assessed. The study shows that adherence to good practices is a necessary but not sufficient condition for early success. Among the six good practices, two are shown to be particularly decisive for the success of regulatory impact assessment reforms, namely, formal integration of regulatory impact assessment in policy making and the presence of a regulatory oversight unit. The second part of the study analyzes regulatory impact assessment reforms that did not produce early success despite adhering to good practices. The study tests several hypothetical reasons for slow developments. It points to the importance of donor flexibility and patience and the need for building reform constituencies inside and outside government. The traditional orthodoxy of regulatory impact assessment reforms as an extension of red tape reduction is challenged. The paper finally presents several possible policy implications of the findings.